A Novel Nanosystem Realizing Curcumin Delivery Based on Fe3O4@Carbon Dots Nanocomposite for Alzheimer’s Disease Therapy - Kuang, Ying; Zhang, Jingwen; Xiong, Mogao; Zeng, Weijia; Lin, Xiaofeng; Yi, Xiaoqing; Luo, Yan; Yang, Min; Li, Feng; Huang, Qitong (Frontiers in Bioengineering and Biotechnology, 2020)
Alzheimer's disease (AD) is the most common neurodegenerative disease, which seriously affects human health but lacks effective treatment methods. Amyloid β (Aβ) aggregates are considered a possible target for AD treatment. Evidence is increasingly showing that curcumin (CUR) can partly protect cells from Aβ-mediated neurotoxicity by inhibiting Aβ aggregation. However, the efficiency of targeted cellular uptake and bioavailability of CUR is very low due to its poor stability and water-solubility. In order to better improve the cell uptake efficiency and bioavailability of CUR and reduce the cytotoxicity of high-dose CUR, a novel CUR delivery system for AD therapy has been constructed based on the employment of the Fe3O4@carbon dots nanocomposite (Fe3O4@CDs) as the carrier. The CUR-Fe3O4@CDs have a strong affinity toward Aβ and effectively inhibit extracellular Aβ fibrillation. In addition, CUR-Fe3O4@CDs can inhibit the production of reactive oxygen species (ROS) mediated by Aβ fibrils and the corresponding neurotoxicity in PC12 cells. More importantly, it can restore nerve damage and maintained neuronal morphology. These results indicate that the application of CUR-Fe3O4@CDs provides a promising platform for the treatment of AD.